Respuesta agronómica de híbridos de maíz (Zea mays L.) a programas de nutrición foliar complementarios a fertilización edáfica, en la zona de Puebloviejo - Veas Parrales, Alexis Rodolfo (2019)
. SUMMARY The present investigation was carried out in the lands of the "Don Adolfo" farm, located in the La Felicita, San Juan sector, Puebloviejo, on the San Juan-Puebloviejo highway. Two maize hybrids and four fertilization programs were investigated, in three replications. The objective of the work was to evaluate the application of the programs in the production of the proposed hybrids. The planting of corn was done with the materials ADV-9313 and S-505 in experimental units of 20 m2. The treatments were distributed in a split plot design. The evaluation of means was performed with the Tukey significance test at 5 %. The evaluated variables were: height of plant, height of insertion, days to flowering, days to harvest, diameter of ears of corn, length of ears, relation grain-gopher, weight of grain, yield per hectare and economic analysis. The results show that the highest grain yield was obtained in the hybrid ADV-9313 seeded at 62 500 plants / ha and fertilized with Program 1 (160 kg/ha N, 30 kg/ha P, 90 kg/ha K, 30 kg/ha S, 20 kg/ha Mg, 3 kg/ha Zn, 2 kg/ha B) with 10 166,67 kg/ha. In addition, the same material showed the highest profit and net benefit. The agronomic efficiency shows that the DK-76508 sown to 95 238 plants/ha and fertilized with the Program 1 (Folizyme GA 1,0 L/ha + Rood Feed 1,0 L/ha), had the best assimilation rate. Keywords: Corn, edaphic fertilization, foliar nutrition